Immunobiology of Long Noncoding RNAs - Atianand, Maninjay K; Caffrey, Daniel R; Fitzgerald, Katherine A (Annual review of immunology, 2017)
The discovery of long noncoding RNAs (lncRNA) has provided a new perspective on gene regulation in diverse biological contexts. lncRNAs are remarkably versatile molecules that interact with RNA, DNA, or proteins to promote or restrain the expression of protein-coding genes. Activation of immune cells is associated with dynamic changes in expression of genes, the products of which combat infectious microorganisms, initiate repair, and resolve inflammatory responses in cells and tissues. Recent evidence indicates that lncRNAs play important roles in directing the development of diverse immune cells and controlling the dynamic transcriptional programs that are a hallmark of immune cell activation. The importance of these molecules is underscored by their newly recognized roles in inflammatory diseases. In this review, we discuss the contribution of lncRNAs in the development and activation of immune cells and their roles in immune-related diseases. We also discuss challenges faced in identifying biological functions for this large and complex class of genes.